Soybean [Glycine max (L.) Merrill] rhizobial diversity in Brazilian oxisols under various soil, cropping, and inoculation managements - Loureiro, Maria de Fátima; Kaschuk, Glaciela; Alberton, Odair; Hungria, Mariangela (Biology and fertility of soils, 2007)
In this study, soybean nodules were collected from 12 sites in the State of Mato Grosso, in the Brazilian Cerrados, where both exotic soybean [Glycine max (L.) Merrill] and bradyrhizobial strains have been introduced from 1 to 18 years before. All soils were originally devoid of rhizobia capable of effectively nodulating soybean and varied in terms of chemical and physical properties, inoculation procedures, and cropping systems. Rhizobial genetic diversity was assessed on 240 isolates by rep-PCR fingerprinting with BOX primer, and indices of diversity (abundance-based coverage estimator and traditional and modified Shannon indices) were applied to the profiles obtained. The genetic diversity was much greater than expected, as after the introduction of a maximum of four strains, up to 13 profiles were identified, some sharing many similar bands with the inoculant strains, but others quite distinct from the putative parental genotypes. The increase in the number of rep-PCR profiles could be attributed to genetic variability due to the stressful tropical environmental conditions, but also might indicate that indigenous rhizobia become capable of nodulating the host legume. After the third year of cropping with the host legume, inoculation did not affect rhizobial diversity. A high content of clay decreased diversity in comparison with that seen in a sandy soil, probably due to reduced aeration. Diversity was higher under the no-tillage system when compared to the conventional tillage management, highlighting the importance of maintaining crop residues in tropical soils. Understanding the ecology of exotic rhizobia after being introduced into new cropping areas represents a first step towards the establishment of better strategies of inoculation, which in turn may result in sustainability and higher plant yields.